Dynamic Systems Modeling for Sustainable Economic Empowerment in Cilacap - Anwar, Nurul; Triana, Nita; Kusumastuti, Dani (Economic Journal of Emerging Markets, 2011)
This paper investigates the dynamic problem of living system in Kampung Laut, Cilacap, which includes social problems and ecological changes. The paper uses a dynamic system model to structure the problems. The model simulates various feasible scenarios, from which the best becomes the base to impose a policy to empower their sustainable economy. The model conceptualizes variables related to the problem to build a figure of Causal Loop Diagram (CLD), which is then simulated using Powersim 2.5 software package. Using the scenario of intensification and population control, the paper finds that it can increase the people’s income, with positive trend until the end of simulation. Keywords: Dynamic modelling, sustainable economic empowerment, causal loop diagram